Ticari işlemlerde taşınır rehni sözleşmesi - Baydak, Ecrin (My University, 2018)
Taşınırların yaygın bir teminat aracı olmasının önündeki en büyük engel, taşınır rehninin teslime bağlı olarak kurulmasıdır. Bu engelin ortadan kaldırılması amacıyla, sicilli taşınır rehni sistemleri oluşturulmuştur. 1971 tarihli 1447 sayılı Ticarî İşletme Rehni Kanunu ile düzenlenen ticarî işletme rehni de bir sicilli taşınır rehni türüdür. Ancak, bu Kanun çeşitli gerekçelerle yetersiz kalmış ve beklentileri karşılayamamıştır. Bu nedenle, 1447 sayılı Kanun yürürlükten kaldırılarak; temel amacı aynı sayılabilecek ve fakat 1447 sayılı Kanun’a göre birçok farklı ve yeni düzenlemeler içeren, 6750 sayılı Ticarî İşlemlerde Taşınır Rehni Kanunu 01.01.2017 tarihinde yürürlüğe konulmuştur. Çalışmamızda; 6750 sayılı Kanun’un amacı, rehin hakkının hukuki niteliği, rehin hakkına hâkim ilkeler, rehin sözleşmesinin niteliği, tarafları, konusu, şekli, rehnin kuruluşu, rehin sözleşmesinin hükümleri ile rehin sözleşmesinin ve rehin hakkının sona ermesi incelenmiştir.

The most prominent problem for using movable assets more commonly as a tool for collateral in commercial transactions is that they are pledged conditional upon transfer of possesion to the pledgee.With the aim of providing a solution to that problem, movable pledges registry systems are formed. The commercial enterprise pledge as was regulated by the Law on Commercial Enterprise Pledges no. 1447 and dated 1971 is also a type of registered movable pledge. However, the aforementioned law, for various reasons, has been insufficient and has failed to meet expectations. Accordingly, the law no. 1447 was repealed, and the Law no. 6750 the Law on Pledges over Movable Assets in Commercial Transactionshas been enacted on 01.01.2017, with a similar purpose but also contains many different and new regulations compared to its predecessor.Our study examines the purpose of the law no. 6750, the legal characteristics of pledges, the principles governing pledges, the legal characteristics of a pledge agreement, and parties, conclusion, subject, form, terms and the termination of a pledge agreement and extinction of pledge.
Keywords: collateral; commercial enterprise pledge; Commercial law; movable asset; movable pledge in commercial transactions; pledge agreement; pledged movables’ registry; Pledges (law); registered movable pledge; Rehin (Hukuk); rehin hakkı; rehin sözleşmesi; rehinli taşınır sicili; right of pledge; sicilli taşınır rehni; taşınır varlık; teminat; Ticaret hukuku; ticarî işlemlerde taşınır rehni; ticarî işletme rehni; Turkey; Türkiye